Rigidez arterial no diabetes mellitus: avaliação vascular discriminativa e sua associação com aptidão cardiorrespiratória - Monteiro, Clara Italiano (2020)
Arterial stiffness (AS) is considered a marker of cardiovascular disease (CVD) and has an accelerated process in the presence of type 2 diabetes mellitus (T2DM) due to several factors. The gold standard measure of AS is the carotid-femoral pulse wave velocity (cfPWV) although other variables, such as the augmentation index (AIx), have been used as an alternative measure for this evaluation. Despite the importance of AS, there is still a need for more evidence in specific populations and at higher cardiovascular risk as in T2DM. Although some studies have established reference values for cfPWV in different populations, individuals with T2DM have been excluded from the analyzes and thus the identification of a specific cutoff point for this population can be very clinically useful for greater precision in the estimation of CVD risk. In view of this gap, the first study was accomplished with the suggestion of a preliminary cutoff value of cfPWVfor this population in order to improve the identification of the AS outcome, as well as to observe the discriminative characteristics. In addition, it is known that the vascular system is an important component and is closely related to performance in physical exercise and, consequently, to cardiorespiratory fitness (CRF), which is known to be impaired in individuals with T2DM. Therefore, following this reasoning, the second study investigated the association between AS variables and CRF assessed by oxygen uptake and the oxygen uptake efficiency slope obtained through the cardiopulmonary exercise test on a treadmill. In conclusion, it is possible to understand a little more about AS in individuals with T2DM and, more specifically, to suggest an indicative of discriminative value for cfPWV as well as to identify the association of AS with CRF. These results can assist the clinical and rehabilitative management of the population of individuals with T2DM considering potential risks and subsequent cardiovascular health care.